Insulin effects on DNA internucleosomal fragmentation and PARP-1 activity in rat liver and thymus cell nuclei - A. V. Margaryan (ՀՀ ԳԱԱ հրատ.)
Tissue homeostasis is maintained by a dynamic balance between cell proliferation and cell death which is mainly executed in the form of apoptosis in normal physiological conditions. In this work the effect of insulin was studied, as a strong survival factor, on the internucleosomal DNA fragmentation as a widely accepted hallmark of apoptosis. The isolated rat liver and thymocyte nuclei were examined after 24 hours of in vivo hormone administration. Enzymatic activity changes of poly(ADP-rybose) polymerase-1 (PARP-1) were evaluated as playing a pivotal role in apoptosis. The results obtained indicate that in 24 hours of insulin action, thymocytes revealed a delay in apoptotic DNA fragmentation. In contrast, liver nuclei displayed an increased fragmentation intensity. Insulin had a notable effect on PARP-1 only in thymocyte nuclei, where it significantly lowered the enzyme’s basal activity. Հյուսվածքային հոմեոստազը պահպանվում է բջիջների աճի և մահվան դինամիկ հավասարակշռության շնորհիվ: Հայտնի է, որ բջջի ֆիզիոլոգիական մահը հիմնականում իրականանում է ապոպտիկ ճանապարհով: Ներկայացված աշխատանքում ուսումնասիրվել է գոյատևման հզոր գործոն` ինսուլինի, ազդեցությունը ԴՆԹ-ի ինտերնուկլեոսոմային ֆրագմենտավորման և պոլի(ԱԿՖ-ռիբոզ) պոլիմերազ-1-ի (ՊԱՌՊ-1) ակտիվության վրա, քանի որ վերջիններս ապոպտոզի բնորոշ հատկանիշներ են: Ստացված արդյունքները ցույց են տալիս, որ ինսուլինի in vivo ազդեցությունից 24 ժ հետո, առնետի թիմոցիտների մեկուսացված կորիզներում ԴՆԹ-ի ապոպտիկ ֆրագմենտավորումը դանդաղում է, ի հակադրություն լյարդի կորիզների, որոնց մոտ դիտվում է ֆրագմենտավորման ինտենսիվության աճ: ՊԱՌՊ-1-ի ակտիվության վրա ինսուլինը դրսևորում է նկատելի ազդեցություն միայն թիմոցիտների կորիզներում` զգալիորեն իջեցնելով ֆերմենտի բազային ակտիվությունը: Гомеостаз тканей осуществляется путем динамического баланса между клеточной пролиферацией и гибелью, которая в нормальных физиологических состояниях в основном протекает в форме апоптоза. В настоящей работе нами было исследовано действие инсулина, мощного фактора выживания, на интернуклеосомальную фрагментацию ДНК и активность поли(АДФ-рибоз) полимеразы-1 (ПАРП-1), которые являются основными признаками апоптоза. Наши данные показали, что in vivo воздействие инсулина через 24 ч приводит к замедлению интернуклеосомальной фрагментации ДНК в ядрах тимоцитов крыс, в то время как в ядрах клеток печени наблюдается увеличение интенсивности фрагментации ДНК. Инсулин проявляет заметное воздействие на активность ПАРП-1 только в ядрах тимоцитов, значительно снижая базовую активность фермента.
Keywords: Biology; Cell Biology; Molecular Biology; Immunology